Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Modal pada Kabupaten dan Kota di Provinsi Daerah Istimewa Yogyakarta (DIY) Tahun 2016–2020 - Imam Khulwani; Risal Rinofah; Pristin Prima Sari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to determine the effect of Regional Original Income, General Allocation Funds, Special Allocation Funds, partially and simultaneously effecting Capital Expenditures in Regencies/Cities in the Province of the Special Region of Yogyakarta (DIY) in 2016-2020. The type of research used is the type of quantitative research. Secondary data obtained from the website (http://www.djpk.kemenkeu.go.id). In this study, it was analyzed using descriptive analysis and multiple linear regression analysis and processed with SPSS version 25. The results of this study indicate that partially: the Regional Original Income (PAD) variable has a partial effect on Capital Expenditures in 4 regencies and 1 city in the Special Region of Yogyakarta (DIY), the General Allocation Fund (DAU) does not partially affect Capital Expenditures. , the Special Allocation Fund (DAK) has an effect on Capital Expenditures in 4 districts and 1 city in the Province of the Special Region of Yogyakarta (DIY). Meanwhile, simultaneously: Variables of Local Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) simultaneously have a significant effect on Capital Expenditures in 4 districts and 1 city in the Special Region of Yogyakarta (DIY). ) with the period 2016-2020. Keywords: Regional Original Revenue, General Allocation Fund, Special Allocation Fund, Capital Expenditure.